Perspectives in Ethology 1976
DOI: 10.1007/978-1-4615-7572-6_7
|View full text |Cite
|
Sign up to set email alerts
|

The Organization of Aggression and Fear In Vertebrates

Abstract: I. ABSTRACTThis chapter considers what factors influence the occurrence of attack and fear behavior (e.g., immobility, flight, distress signals). It is argued that, with the exception of conditioned attack and fear behavior, the same types of basic situations are capable of evoking either type of response.These situations are as follows: (l) Pain. (2) A moving object coming too close to an animal (individual distance intrusion). (3) A novel object or animal entering another's familiar area: this includes not o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
48
1

Year Published

1980
1980
2007
2007

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(52 citation statements)
references
References 259 publications
(298 reference statements)
0
48
1
Order By: Relevance
“…Previous studies identify other differences, such as the lunge-and-bite attack shown by cats only during aggression; submissive postures and ultrasound are shown by rats only during submission [29,30]. Our results, however, reveal that the different motor pattern of defense and attack during aggression is not species-specific, it could be related among different species of vertebrates.…”
Section: Discussioncontrasting
confidence: 57%
“…Previous studies identify other differences, such as the lunge-and-bite attack shown by cats only during aggression; submissive postures and ultrasound are shown by rats only during submission [29,30]. Our results, however, reveal that the different motor pattern of defense and attack during aggression is not species-specific, it could be related among different species of vertebrates.…”
Section: Discussioncontrasting
confidence: 57%
“…It has been suggested by various behavioural theorists (e.g. Archer, 1976;Inglis, 1983;Salzen, 1962) that the degree to which an animal is stimulated by an event or situation is dependent on the discrepancy between his/her expectations of stimulation and the actual stimulation he/she receives. Additionally, these theorists propose that the immediate psychological goal of behaviour is to control the level of stimulation the animal receives from his/her surroundings.…”
Section: Animal Welfare Implicationsmentioning
confidence: 99%
“…Males of a variety of rodent species will attack a strange conspecific entering their familiar, home or territorial area (Crowcroft 1966;Archer 1976;Koolhaas et al 1980). The intensity of attack depends on the attacker's familiarity with the surrounding area (Jones & Nowell 1973;Mink & Adams 1981;Flannelly et al 1984) and the type of intruder (Alberts & Galef 1973;Archer 1976;Brain et al 1981;Whalen & Johnson 1987).…”
mentioning
confidence: 99%
“…The intensity of attack depends on the attacker's familiarity with the surrounding area (Jones & Nowell 1973;Mink & Adams 1981;Flannelly et al 1984) and the type of intruder (Alberts & Galef 1973;Archer 1976;Brain et al 1981;Whalen & Johnson 1987). Individual differences in aggression measured under standardized conditions have most often been ascribed to genetic and/or hormonal differences between individuals (Lagerspetz 1964;Selmanoffet al 1976;Simon 1979;Van Oortmerssen & Bakker 1981;Hahn & Haber 1982;Albert et al 1986;Van Oortmerssen et al 1987;Whalen & Johnson 1987) and are related to various other characters, such as open-field activity, defecation in an open-field, reactivity to a novel environment, maze performance, etc.…”
mentioning
confidence: 99%